Analisis AsbÄbun NuzÅ«l Ayat-Ayat Ekonomi Melalui Pendekatan Kontekstual - Muthmainnah, Muthia; Imam, Muh. Abdi; Abubakar, Achmad; Ilyas, Hamka (Al-Amwal : Journal of Islamic Economic Law, 2023)
This article examines the Qur'anic verses that are nuzul embodied in economic values in it. The purpose of this study is to expose the Islamic economic values contained in these verses, and relate them to the development of the current era. There are seven economic verses that have sabab nuzul. Of the seven verses, the author categorizes them into four themes, namely related to consumption, related to distribution, related to wadiah (deposits), and related to qard (accounts receivable). The type of research applied is qualitative research with a focus on literature studies. The method of data collection and analysis is based on a normative descriptive approach that emphasizes the evaluation of the sources of data found. To strengthen the research foundation, researchers use a comprehensive and in-depth literature review approach that is in accordance with the topic discussed. The results of this study reveal that the application of economic principles contained in the Qur'an through asbabun nuzul analysis can help direct economic practices in the modern era that are fair, honest, free from usury and everything that is forbidden, and able to reduce economic inequality.Artikel ini mengkaji perihal ayat-ayat Alquran yang berasbabun nuzul yang termaktub nilai-nilai ekonomi di dalamnya. Tujuan penelitian ini untuk membeberkan nilai-nilai ekonomi Islam yang ada di dalam ayat-ayat tersebut, serta menghubungkannya dengan perkembangan zaman saat ini. Terdapat tujuh ayat-ayat ekonomi yang mempunyai sabab nuzul. Dari tujuh ayat tersebut penulis mengkategorikannya dalam empat tema yakni terkait konsumsi, terkait distribusi, terkait wadiah (titipan), serta terkait qard (utang piutang). Tipe penelitian yang diterapkan adalah penelitian kualitatif dengan fokus pada studi pustaka. Metode pengumpulan dan analisis data didasarkan pada pendekatan deskriptif normative yang menekankan evaluasi sumber-sumber data yang ditemukan. Untuk menguatkan landasan penelitian, peneliti menggunakan pendekatan tinjauan literatur yang komprehensif dan mendalam yang sesuai dengan topik yang dibahas. Hasil penelitian ini mengungkapkan bahwa penerapan prinsip-prinsip ekonomi yang terdapat dalam Alquran melalui analisis asbabun nuzul dapat membantu mengarahkan praktik ekonomi di era modern yang adil, jujur, terbebas dari riba dan segala yang diharamkan, serta mampu mengurangi kesenjangan ekonomi.Â